Portable and foldable wet clothes hanger - Mohamad Ruzaini, Mohamed Ibrahim (2008)
The clothes hanger is used to hang the wet clothes that are washed. Development of this portable and foldable wet clothes hanger is to create a new model of clothes hanger that is foldable and portable and to fullfill current market needs. To design and fabricated this portable and foldable clothes hanger, it must be compared with other product that maybe available in the market. First, get an idea from internet, magazine, newspaper or other from available data. Form there the information and idea to design and fabricated can be created. The whole project involved various method and process that usually use in engineering such as concept design, analysis process and lastly fabrication process. This portable and foldable wet clothes hanger is made from aluminium. The height of this hanger can be adjusted according to users taste. It also can be easily moved because of its size and weight. When it is not used, it can be folded and only needed small place to store. Overall from this project, time management and discipline is important to make sure this project goes smooth as plan and done at correct time.